2002
DOI: 10.1152/japplphysiol.00526.2001
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the endocrine and metabolic responses to hypoxic exercise

Abstract: Sandoval, Darleen A., and Kathleen S. Matt. Gender differences in the endocrine and metabolic responses to hypoxic exercise. J Appl Physiol 92: 504-512, 2002; 10.1152/ japplphysiol.00526.2001.-This study tested the hypothesis that women would have blunted physiological responses to acute hypoxic exercise compared with men. Fourteen women taking oral contraceptives (28 Ϯ 0.9 yr of age) and 15 men (30 Ϯ 1.0 yr of age) with similar peak O 2 consumption (V O2 peak) values (56 Ϯ 1.1 vs. 57 Ϯ 0.8 ml ⅐ kg fat-free m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…-----Similar findings, reflecting the gender difference, were reported by Sandoval et al [22] after 5 min cycling corresponding to 60%VO 2 max in recreationally active men and women, and they postulated that if women were using less glycogen during exercise than they would produce less lactate. Moreover Sargent et al [23] noted that in untrained men lactate concentration reached higher values then in untrained women after cessation of incremental exercise test.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…-----Similar findings, reflecting the gender difference, were reported by Sandoval et al [22] after 5 min cycling corresponding to 60%VO 2 max in recreationally active men and women, and they postulated that if women were using less glycogen during exercise than they would produce less lactate. Moreover Sargent et al [23] noted that in untrained men lactate concentration reached higher values then in untrained women after cessation of incremental exercise test.…”
Section: Discussionsupporting
confidence: 76%
“…However, investigation of the effect of gender on exercise substrate utilization yielded conflicting results. The mechanisms for these gender-based differences are still not fully understood, but it was postulated that substrate metabolism can be influenced by the catecholamines and female sex hormones [22], body fat content, percent of fiber type area and training experience [21]. Elis et al [9] revealed that estradiol increases the availability of lipids to exercising muscle due to an increase in muscle lipoprotein lipase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of epinephrine has been suggested to be responsible for the rise in blood glucose levels and reduction in insulin sensitivity [14,15], however in one study, epinephrine levels remained unchanged despite a rise in blood glucose, indicating alternative metabolic signalling pathways [17]. Additionally hormones such as oestrogen may affect the response to hypoxic training as seen with gender differences in glucose response to hypoxic training [17]. Current studies favour a chronic, moderate level of hypoxic training (1,500m to 2,500m) used with moderate level of exercise intensity (55% -65% HR max ) to improve blood glucose regulation.…”
Section: Blood Glucosementioning
confidence: 95%
“…It would also suggest that patients with issues with blood regulation should monitor their blood glucose status when participating in hypoxic training involving high exercise intensities or high levels of hypoxia. Secretion of epinephrine has been suggested to be responsible for the rise in blood glucose levels and reduction in insulin sensitivity [14,15], however in one study, epinephrine levels remained unchanged despite a rise in blood glucose, indicating alternative metabolic signalling pathways [17]. Additionally hormones such as oestrogen may affect the response to hypoxic training as seen with gender differences in glucose response to hypoxic training [17].…”
Section: Blood Glucosementioning
confidence: 97%
See 1 more Smart Citation